MANAJEMEN KURIKULUM INTEGRATIF MADRASAH - PESANTREN (Studi Multisitus di MAN 1 Malang dan Madrasah Terpadu MAN 3 Malang) - Muhammad Rouf (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
Mulyasa worries this decline is an evidence of a shift towards value destruction, or the creation of new values based on pragmatism, materialism, hedonism, secularism, even atheism. In forming the character or noble character, Indonesia has long been a successful model of education, formed the character of the nation's children in the education system of